Exploration of The Merdeka Belajar Kampus Merdeka (MBKM) Curriculum Policy in The Early Childhood Islamic Education Study Program in Indonesia - Danang Prastyo; Herlina Herlina; Kholisussa’di Kholisussa’di; Aries Edy Nugroho; Wiwin Yulianingsih; Ardhana Reswari; Nanda Mustika Meilan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to explore the development of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in the PIAUD study program in Indonesia. This research adopts a qualitative descriptive approach with a literature review method. The subjects of this research are faculty members and curriculum developers from the PIAUD study programs at State Islamic University of Syekh Nurjati Indonesia, State Institute for Islamic Studies of Kudus, and State Islamic University of Sayyid Ali Rahmatullah Tulungagung. Data collection techniques involve literature study, and data analysis techniques employ data reduction and data identification. The results of the study reveal that the MBKM curriculum is a designed framework that addresses the challenges of the 21st century by emphasizing the freedom and independence to learn various fields of knowledge. The development of the MBKM curriculum consists of five stages: preparation, planning, development, implementation, and evaluation. Its implementation comprises nine key activities such as curriculum adjustment, collaboration with partners, and continuous assessment.